Routledge international handbook of play, therapeutic play and play therapy - Jennings, Sue, 1938-; Holmwood, Clive (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The Routledge International Handbook of Play, Therapeutic Play and Play Therapy is the first book of its kind to provide an overview of key aspects of play and play therapy, considering play on a continuum from generic aspects through to more specific applied and therapeutic techniques and as a standalone discipline. Presented in four parts, the book provides a unique overview of, and ascribes equal value to, the fields of play, therapeutic play, play in therapy and play therapy. Chapters by academics, play practitioners, counsellors, arts therapists and play therapists from countries as diverse as Japan, Cameroon, India, Czech Republic, Israel, USA, Ireland, Turkey, Greece and the UK explore areas of each topic, drawing links and alliances between each. The book includes complex case studies with children, adolescents and adults in therapy with arts and play therapists, research with children on play, work in schools, outdoor play and play therapy, animal assisted play therapy, work with street children and play in therapeutic communities around the world. The Routledge International Handbook of Play, Therapeutic Play and Play Therapy demonstrates the centrality of play in human development, reminds us of the creative power of play and offers new and innovative applications of research and practical technique. It will be of great interest to academics and students of play, play therapy, child development, education and the therapeutic arts. It will also be a key text for play and creative arts therapists, both in practice and in training, play practitioners, social workers, teachers and anyone working with children"--
OCLC-licensed vendor bibliographic record.
Keywords: Play therapy -- Handbooks, manuals, etc; Child psychotherapy -- Handbooks, manuals, etc; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health